2003
DOI: 10.1177/0145482x0309701007
|View full text |Cite
|
Sign up to set email alerts
|

A Haptic Glove as a Tactile-Vision Sensory Substitution for Wayfinding

Abstract: A prototype of a device that relays navigational information to a person who is visually impaired using a portable tactile glove and a wearable computer and camera system was demonstrated and tested. The results of preliminary tests using the glove as a navigational device show that the paths traversed by subjects negotiating an obstacle course using the glove were not qualitatively different from the paths produced with existing wayfinding devices and that hitting probabilities, the measure of the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…Pin matrices permit users more than one point of contact and provide representations that most resemble real world counterparts. However, pin matrices are limited in resolution due to the spacing of the pins; Zelek, Bromley, Asmar, & Thompson, 2003;. A few commercially available devices, however, have been studied extensively for a broad variety of accessibility needs.…”
Section: Hardware Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pin matrices permit users more than one point of contact and provide representations that most resemble real world counterparts. However, pin matrices are limited in resolution due to the spacing of the pins; Zelek, Bromley, Asmar, & Thompson, 2003;. A few commercially available devices, however, have been studied extensively for a broad variety of accessibility needs.…”
Section: Hardware Platformsmentioning
confidence: 99%
“…Several educational studies successfully created virtual reality environments for object exploration, emphasizing the benefits of providing guided exploration , reference points , and clear boundaries (Bernareggi, Mussio, & Parasiliti Provenza, 2009;Jones et al, 2014) (Marston, Loomis, Klatzky, & Golledge, 2007), and feedback about the surrounding area . The majority of these articles showed that haptic feedback is particularly useful for aiding in obstacle avoidance A c c e p t e d M a n u s c r i p t 12 (Hill & Black, 2003;Zelek et al, 2003;Simpson et al, 2005;Ghiani, Leporini, & Paterno, 2009 The need to address challenges in education, navigation, and computer accessibility remains relevant today, and recent research continues to focus on all of these problems. As accessibility research moves forward, it must address the needs of device users as reflected by these past research trends, while adapting to new needs that arise as technology continues to change.…”
Section: Applications Of Assistive Devicesmentioning
confidence: 99%
“…It has been reported that tactile interaction can effectively assist pedestrians with visual impairments when crossing the street [Ross and Blasch 2000]. As tactile-based navigational aids, vibrotactile stimulation systems have been proposed using several vibrators in the shape of a cap [Cassinelli et al 2006], rings [Amemiya et al 2004], a vest [Erp et al 2005], a belt Tan et al 2003;Tsukada and Yasumura 2004], and a glove [Zelek et al 2003]. Unfortunately, these tactile approaches require that users learn how to convert stimuli to information; this is not intuitive and requires training since the tactile stimuli employed are basically nondirectional.…”
Section: Related Workmentioning
confidence: 99%
“…Several effect libraries are available to designers of vibrotactile (VT) sensations, e.g., for accessible wayfinding [6] or media experiences [7]- [10]. But despite the need for effect customizability [11], VT library elements are generally opaque in construction and immutable.…”
Section: Introductionmentioning
confidence: 99%